A method for preparing a negative electrode sheet of a nickel-zinc alkaline battery and its application

By using the dual protective structure of the carbon zinc oxide and the PVA film protection layer, the corrosion, branch crystal and hydrogen analysis of zinc battery in nickel and zinc batteries are solved, and the cycle stability and Kuron efficiency of the battery significantly improve the battery.

CN114335446BActive Publication Date: 2025-01-28SOUTH CHINA UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210081348.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-24
Publication Date
2025-01-28
Estimated Expiration
2042-01-24

AI Technical Summary

Technical Problem

The cycling performance of nickel-zinc alkaline batteries is poor and the Coulombic efficiency is low, mainly due to the corrosion of zinc negative electrode, dendrite growth and hydrogen evolution reaction problems, and these problems affect each other, resulting in low stability and efficiency of the battery.

Method used

The carbon -wrap zinc oxide is used as the negative electrode material, and the carbon shell layer with a higher graphite is covered by the gas sedimentation method, combined with the PVA thin film protective layer to form a dual protection structure to suppress the uneven deposition of zinc and the growth of the branch crystal.

Benefits of technology

It significantly improves the cycle stability of the nickel-zinc battery and the efficiency of Kuron. The discharge ratio has a capacity of 630mA · H G-1, Kuron's efficiency is as high as 97%, and it can maintain a stable performance of 500 laps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114335446B_ABST
    Figure CN114335446B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nickel-zinc alkaline battery preparation, and discloses a method for preparing a negative electrode sheet of a nickel-zinc alkaline battery and its application. The method comprises the following steps: uniformly mixing a negative electrode active material, a conductive agent and a binder, dropping N-methylpyrrolidone and stirring for 10 to 15 hours to obtain a uniform slurry, dropping and / or coating the slurry on a current collector, drying to obtain a sheet, placing the sheet in an immersion solution for 1 to 5 minutes, and drying to form a diaphragm to obtain a negative electrode sheet. The negative electrode sheet with dual protection of carbon coating and thin film layer of the invention not only significantly improves the service life of the alkaline nickel-zinc battery by inhibiting the generation of zinc dendrites, but also improves the capacity and coulomb efficiency of the negative electrode by inhibiting hydrogen evolution reaction and zinc self-reaction. The negative electrode material and the method for preparing the negative electrode sheet of the invention are convenient and simple to operate, and are easy to implement and prepare on a large scale. The nickel-zinc battery prepared by the invention is convenient to assemble, has a long service life and does not generate dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nickel-zinc alkaline battery preparation, and in particular to a method for preparing a negative electrode sheet of a nickel-zinc alkaline battery and application thereof. Background Art

[0002] At present, the secondary batteries with large-scale commercial applications mainly include lead-acid batteries, nickel-metal hydride batteries and lithium-ion batteries. However, they all have certain limitations. For example, the low energy density and environmentally harmful characteristics of lead-acid batteries make them face elimination; the low operating voltage and power density, as well as the limited service life restrict the promotion and application of nickel-metal hydride batteries; lithium batteries are limited by flammable and high-viscosity organic electrolytes, high manufacturing costs and limited lithium and cobalt resources, etc., and there are great safety hazards in large-scale applications, and the fast charging and discharging capabilities are poor, and the cost remains high. In the context of building a green and harmonious society and achieving the goal of carbon neutrality, there is an urgent need for a green, environmentally friendly, safe, and high energy storage battery. Among the many known battery systems, alkaline nickel-zinc batteries, as green and environmentally friendly aqueous batteries, are the most likely type of batteries to meet the above requirements. They have the advantages of high power, rich electrode material resources, and excellent safety performance. They are considered to be a strong competitor and substitute for lithium batteries, lead-acid batteries, and nickel-metal hydride batteries.

[0003] Although alkaline nickel-zinc batteries have many advantages and have a history of more than 200 years since they were proposed, their promotion and application have been slow. Currently, commercially available batteries are very limited and have poor performance. The main reason for this phenomenon is the poor cycle performance and low coulomb efficiency of the battery, and many problems related to the zinc negative electrode are the key, including the corrosion of electrode materials, the growth of zinc dendrites and hydrogen evolution reaction. Moreover, these problems are not independent of each other, but affect each other. Specifically, the formation of dendrites will lead to an increase in the surface area of ​​the negative electrode, which will accelerate the oxidation and corrosion dissolution of zinc and increase the hydrogen evolution rate (zinc oxidation is accompanied by hydrogen evolution); in addition, some products of zinc oxidation will cover the surface of the material to form an inert layer, reducing the reactivity of zinc, thereby exacerbating the hydrogen evolution ratio during the charge and discharge process. The corrosion and dissolution of dendrites and electrode materials are the main reasons for the poor cycle stability of nickel-zinc batteries, while the self-corrosion (self-discharge) of electrode materials and hydrogen evolution reaction are the main reasons for their low coulomb efficiency.

[0004] In order to alleviate the related problems of zinc anode, various strategies have been proposed, such as the use of additives, surface modification and material structure optimization. Physical mixing of additives with anode materials is the simplest way to change the material properties. Among them, the metal oxide additive Ca(OH)2 has been studied the most. The formation of calcium zincate reduces the solubility of zincate in the electrolyte and reduces the dissolution of the zinc anode. However, the formation and decomposition of calcium zincate are slow, resulting in poor high-rate charge and discharge performance of the battery. In addition, there are some research reports on the use of carbon for related coating modifications, such as graphite oxide (GO) and TiN x O y Coating (YanY, Zhang Y, Wu Y, Wang Z, Mathur A, Yang H, et al. A Lasagna-Inspired Nanoscale ZnO Anode Design for High-Energy Rechargeable Aqueous Batteries. ACS Applied Energy Materials. 2018; 1: 6345-51.). However, the coulombic efficiency and durability of these systems are far from satisfactory for practical applications. There is still a long way to go to balance the discharge voltage, durability, reversible capacity and power density of ZnO-based anodes. It is necessary to find a more comprehensive solution to balance the discharge voltage, durability, reversible capacity and power density of the anode. Therefore, the present invention mainly addresses the above-mentioned problems of zinc negative electrode and proposes a two-layer protection method to solve the effective solution of zinc dendrites and self-dissolution. Summary of the invention

[0005] The primary purpose of the present invention is to provide a method for preparing a negative electrode sheet of a nickel-zinc alkaline battery, which effectively solves various problems existing in the zinc negative electrode.

[0006] Another object of the present invention is to provide a negative electrode plate for a nickel-zinc alkaline battery.

[0007] Another object of the present invention is to provide an application of the above-mentioned negative electrode plate, which is used in the assembly of alkaline nickel-zinc batteries, so that efficient and stable nickel-zinc batteries have a basis for industrial application.

[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0009] A method for preparing a negative electrode sheet of a nickel-zinc alkaline battery comprises the following steps:

[0010] A1: Preparation of negative electrode materials: Mix the negative electrode active material, conductive agent and binder in proportion, add solvent and stir for 10-15 hours to obtain a uniform slurry;

[0011] A2: Adding negative electrode material: Add the slurry dropwise and / or apply it on the current collector, and then dry it to obtain the electrode sheet;

[0012] A3: Preparation of negative electrode: put the electrode in A2 into the soaking solution for 1 to 5 minutes, and obtain the negative electrode after drying;

[0013] The negative electrode active material in step A1 is carbon-coated zinc oxide, and the concentration of the soaking solution in step A3 is 0.05-0.1 g / mL.

[0014] Preferably, in step A1, the weight ratio of the negative electrode active material, the conductive agent and the binder is (70-90): (5-20): (5-20), and the ratio of the mass of the solvent to the total mass of the negative electrode active material, the conductive agent and the binder is (10-15): 1; the soaking liquid in step A3 is a polyvinyl alcohol solution, and the concentration of the soaking liquid is 0.0875 g / mL.

[0015] Preferably, in step A1, the conductive agent is acetylene black, the binder is one or more of polyvinylidene fluoride, polyvinyl alcohol, hydroxymethyl cellulose and styrene-butadiene rubber, the solvent is water-soluble water or ethanol, or water-insoluble N-methylpyrrolidone or dimethylacetamide; in step A2, the current collector is carbon cloth or graphite paper or copper mesh, and the drying condition is drying at 80-100°C for 12±6h; in step A3, the polyvinyl alcohol model is 1799 or 1797, and the drying is drying at room temperature.

[0016] Preferably, the method for preparing the carbon-coated zinc oxide comprises the following steps:

[0017] (1) mixing zinc salt and oxalic acid, and grinding for 30 to 60 minutes to obtain zinc oxalate;

[0018] (2) heating the zinc oxalate obtained in step (1) to 300-450° C. at a rate of 3-5° C. / min, keeping the temperature for 30-60 min, and cooling to room temperature to obtain zinc oxide;

[0019] (3) The zinc oxide and carbon source in step (2) are heated to 500-800° C. at a rate of 2° C. / min under nitrogen atmosphere and kept at this temperature for 2-5 h. After cooling to room temperature, the zinc oxide is taken out to obtain carbon-coated zinc oxide.

[0020] Preferably, the zinc salt in step (1) is zinc acetate or zinc carbonate, and the mass ratio of the zinc salt to oxalic acid is (2-4):1; the carbon source in step (3) is solid organic matter, and the mass ratio of zinc oxide to the carbon source is 1:(3-6).

[0021] Preferably, the solid organic matter is one or more of phenolic organic matter, ester organic matter, and benzene organic matter.

[0022] Preferably, the solid organic matter is one or more of naphthol, dichlorobenzene and acetic acid glycerol.

[0023] A negative electrode plate of a nickel-zinc alkaline battery is prepared by the above method.

[0024] The application of the above negative electrode plate in the preparation of nickel-zinc alkaline batteries.

[0025] Preferably, the preparation of a nickel-zinc alkaline battery comprises the following steps:

[0026] The zinc negative electrode sheet, the nickel positive electrode sheet and the separator are combined into an electrode group, which is placed in a soft-pack battery, and the electrolyte is injected into the battery soft pack, and the battery is sealed to obtain a nickel-zinc battery;

[0027] The diaphragm is a glass fiber diaphragm, the electrolyte in the electrolyte is potassium hydroxide, the solvent is distilled water or membrane filtered pure water, and saturated zinc oxide is added, the electrolyte concentration is 6.0-7.0 mol / L, and the electrolyte volume is 200-400 μL.

[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0029] (1) The present invention uses zinc salt and oxalic acid as raw materials to prepare nanoparticle zinc oxide, and then uses an organic carbon source to coat a carbon shell layer with a high degree of graphitization through a vapor deposition method. Carbon with a high degree of graphitization has a high electrical conductivity, so the resulting powder material is black; on the other hand, the nanostructure has a shorter ion transmission path, which is conducive to the rapid shuttling of ions; at the same time, the coating of the carbon layer is conducive to alleviating the volume change of the material during the charge and discharge process, and the dissolution and re-deposition of zinc oxide are all carried out in the carbon layer, which can effectively inhibit the uneven deposition of zinc and the growth of zinc dendrites. Therefore, the material has better cycle stability and rate performance.

[0030] (2) The negative electrode plate prepared by the present invention uses the prepared carbon-coated zinc oxide as the active material to make a slurry and apply it on the current collector, and then it is coated with PVA soaking liquid to form a thin film protective layer. The protection of the thin film layer further reduces the contact between the material and water molecules and oxygen, and inhibits the hydrogen evolution reaction. In addition, under the dual protection of the carbon shell layer and the thin film layer, the self-dissolution problem of the zinc oxide negative electrode and the self-reaction problem of zinc in the charged state are significantly improved. Therefore, the negative electrode plate has a higher coulombic efficiency and stable cycle performance in a soft-pack battery with limited electrolyte content, and the battery's discharge specific capacity reaches 630mA·hg -1 , the Coulomb efficiency is as high as 97%, and it can remain stable for 500 cycles.

[0031] (3) The method for preparing the carbon-coated nano-zinc oxide and the surface layer protective negative electrode sheet adopted by the present invention is simple and effective, and the chemical reagents used are all common laboratory medicines. The preparation process and materials are environmentally friendly and harmless, and the obtained negative electrode sheet can be mass-produced, with very high economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a Raman graph of carbon-coated nano-zinc oxide prepared in an embodiment of the present invention.

[0033] Figure 2 Schematic diagram of the structure of a soft-pack battery in an embodiment of the present invention.

[0034] Figure 3 It is a performance test comparison diagram of the embodiments of the present invention and the comparative examples.

[0035] Figure 4 The following are SEM images of the negative electrode sheets of the embodiments of the present invention and the comparative example after cycling. DETAILED DESCRIPTION

[0036] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0037] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0038] Example 1: Preparation of carbon-coated zinc oxide

[0039] The preparation method of carbon-coated zinc oxide comprises the following steps:

[0040] (1) mixing zinc acetate and oxalic acid in a mass ratio of 2:1 in a mortar and grinding for 60 minutes to produce zinc oxalate;

[0041] (2) placing the product obtained in step (1) in a muffle furnace and heating the temperature from room temperature to 450° C. at a rate of 5° C. / min, keeping the temperature for 30 min, cooling to room temperature, and then taking out to obtain white powdered zinc oxide;

[0042] (3) Take the zinc oxide obtained in step (2), use natural camphor balls (main component naphthol) as a carbon source, place the carbon source and zinc oxide powder in a mass ratio of 3:1 in a tube furnace according to the gas flow order, heat to 800°C at a rate of 2°C / min under nitrogen atmosphere protection, keep warm for 3h, cool to room temperature and take out to obtain black powder as carbon-coated zinc oxide.

[0043] Example 2: Nickel-zinc battery assembled with nano-zinc oxide

[0044] Commercial nickel hydroxide is selected as the positive electrode active material, nickel foam is used as the positive electrode current collector, nickel hydroxide, cobalt tetroxide, acetylene black and polytetrafluoroethylene are mixed uniformly in weight proportions of 70, 10, 10 and 10, respectively, to prepare a positive electrode slurry, the prepared slurry is evenly coated on the nickel foam, and then a double-roller machine is used to uniformly press to obtain a positive electrode sheet; the negative electrode uses the nano-zinc oxide prepared by the present invention as the active material, carbon cloth is selected as the negative electrode current collector, zinc oxide, acetylene black and polyvinylidene fluoride are mixed uniformly in weight proportions of 80, 10 and 10, respectively, and ten times the amount (zinc oxide, acetylene black, polyvinylidene fluoride) is added dropwise. N-methylpyrrolidone (NMP) with a mass of ten times the total mass of ethylene is stirred to form a uniform slurry, the prepared slurry is dripped on a carbon cloth of a specific area (a disc with a diameter of 1.3 cm punched out by a punching machine), and dried at 80°C to obtain a negative electrode sheet; a glass fiber separator is selected to separate it from the positive electrode sheet and the negative electrode sheet to form a pole group, which is then placed in a soft bag; potassium hydroxide is dissolved in distilled water to prepare an aqueous solution with a concentration of 6 mol / L, and zinc oxide powder is added to saturation; 200 μL of the clarified liquid of the above solution is taken as an electrolyte, injected into the soft bag, and then sealed to obtain the required nickel-zinc battery.

[0045] Example 3: Nickel-zinc battery with a layer of carbon-coated zinc oxide for protection

[0046] Commercial nickel hydroxide is selected as the positive electrode active material, nickel foam is used as the positive electrode current collector, nickel hydroxide, cobalt oxide, acetylene black and polytetrafluoroethylene are mixed uniformly in weight proportions of 70, 10, 10 and 10, respectively, to prepare a positive electrode slurry, the prepared slurry is evenly coated on the nickel foam, and then a double-roller machine is used to uniformly press to obtain a positive electrode sheet; the carbon-coated zinc oxide prepared by the present invention is selected as the negative electrode active material, carbon cloth is selected as the negative electrode current collector, carbon-coated zinc oxide, acetylene black and polyvinylidene fluoride are mixed uniformly in weight proportions of 80, 10 and 10, respectively, and ten times the amount (zinc oxide, acetylene black, polyvinylidene fluoride) is added dropwise; The obtained slurry is dripped on a carbon cloth of a specific area (a disc with a diameter of 1.3 cm punched out by a punching machine), and dried at 80°C to obtain a negative electrode sheet; a glass fiber separator is selected to separate it from the positive electrode sheet and the negative electrode sheet to form a pole group, which is then placed in a soft bag; potassium hydroxide is dissolved in distilled water to obtain an aqueous solution with a concentration of 6 mol / L, and zinc oxide powder is added until saturated; 200 μL of the clarified liquid of the above aqueous solution is taken as an electrolyte, injected into the soft bag, and then sealed to obtain the required nickel-zinc battery.

[0047] Example 4: Nickel-zinc battery assembled with negative electrode sheet prepared by double protection of carbon-coated zinc oxide and thin film coating

[0048] Commercial nickel hydroxide is selected as the positive electrode active material, nickel foam is used as the positive electrode current collector, nickel hydroxide, cobalt oxide, acetylene black and polytetrafluoroethylene are mixed uniformly in weight proportions of 70, 10, 10 and 10 respectively to obtain a positive electrode slurry, the prepared slurry is evenly coated on the nickel foam, and then a double-roller machine is used to uniformly press to obtain a positive electrode sheet; the nano-sized carbon-coated zinc oxide prepared by the present invention is selected as the negative electrode active material, carbon cloth is selected as the negative electrode current collector, the carbon-coated zinc oxide, acetylene black and polyvinylidene fluoride are mixed uniformly in weight proportions of 80, 10 and 10 respectively, ten times (ten times the total mass of zinc oxide, acetylene black and polyvinylidene fluoride) of N-methylpyrrolidone (NMP) is added dropwise and stirred to form a uniform slurry, the prepared negative electrode slurry is dripped on a carbon cloth of a specific area (a disc with a diameter of 1.3 cm punched out by a punching machine), and the dried carbon cloth is immersed in a PVA gel (3.5 g 1799 type polyvinyl alcohol, molecular weight 44.05, is dissolved in 40ml distilled water in a 85℃ water bath for 1-5min, then taken out and dried at room temperature to obtain a negative electrode sheet; a glass fiber separator is selected to separate it from the positive electrode sheet and the negative electrode sheet to form an electrode group, which is then placed in a soft bag; potassium hydroxide is dissolved in distilled water to prepare an aqueous solution with a concentration of 6mol / L, and zinc oxide powder is added until saturated; 200μL of the clarified liquid of the above solution is taken as the electrolyte, injected into the soft bag, and then sealed to obtain the required nickel-zinc battery.

[0049] Comparative Example 1: Alkaline nickel-zinc battery assembled with commercial zinc oxide

[0050] Commercial nickel hydroxide was selected as the positive electrode active material, and nickel foam was selected as the positive electrode matrix. Nickel hydroxide, cobalt trioxide, acetylene black and polytetrafluoroethylene were mixed uniformly in weight proportions of 70, 10, 10 and 10, respectively, to obtain the positive electrode material. The prepared slurry was evenly coated on the nickel foam, and then evenly pressed by a double-roller machine to obtain the positive electrode sheet. Commercial zinc oxide was selected as the negative electrode active material, and carbon cloth was selected as the negative electrode current collector. Zinc oxide, acetylene black and polyvinylidene fluoride were mixed uniformly in weight proportions of 80, 10 and 10, respectively, and ten times the amount (total weight of zinc oxide, acetylene black and polyvinylidene fluoride) was added dropwise. The obtained negative electrode slurry was dripped on a carbon cloth of a specific area (a disc with a diameter of 1.3 cm punched out by a punching machine), and dried at 80°C to obtain a negative electrode sheet; a glass fiber separator was selected to form a pole group with the positive electrode sheet and the negative electrode sheet, and then put into a soft bag; potassium hydroxide was dissolved in distilled water to prepare an aqueous solution with a concentration of 6 mol / L, and zinc oxide powder was added until saturated; 200 μL of the clarified liquid of the above solution was taken as an electrolyte, injected into the soft bag, and then sealed to obtain the required nickel-zinc battery.

[0051] In order to more clearly illustrate the beneficial effects that can be obtained by implementing the present invention, the outstanding advantages of the nickel-zinc battery assembled with the negative electrode sheet prepared by the present invention are described in detail below in combination with the comparative example; specifically, the specific capacity and stability of the nickel-zinc battery are tested, and the results are shown in detail. Figure 3 In addition, in order to more clearly illustrate that the present invention can inhibit the generation of dendrites, the pole pieces after the cycles of the embodiment and the comparative example were characterized by SEM to explore the changes in their morphology. Figure 4 .

[0052] from Figure 3 It can be seen that the charge capacity is 658mA·hg -1 When the charge and discharge current is 4A / g, commercial zinc oxide (Comparative Example 1) is used as the negative electrode, and its initial discharge specific capacity can reach 600mA·hg -1 , the coulombic efficiency is 90%, but it can only maintain stable operation for less than 200 cycles, and then the specific capacity drops sharply; while the negative electrode using nano-sized zinc oxide (Example 2) can achieve stability of 300 cycles, and then it begins to decay sharply. This shows that the battery cycle performance is not very good when zinc oxide is directly used as the negative electrode active material without any protection. This is mainly caused by corrosion, deformation, dendrites, hydrogen evolution and other problems related to the zinc negative electrode. The zinc oxide negative electrode (Example 3) that has been protected by carbon coating has a discharge specific capacity of 620mA·hg -1 , the coulombic efficiency is 95%, and it can still maintain 550mA·hg after 350 cycles -1 The discharge capacity is significantly better than that of the nickel-zinc battery directly assembled with zinc oxide negative electrode, indicating that carbon coating has a significant improvement on the discharge capacity and stability of the battery. Furthermore, using the negative electrode sheet with double protection of carbon coating layer and film layer (Example 4), the cycle performance of the battery is more significantly improved. After several cycles of activation, the discharge capacity reaches 630mA·hg -1 The coulombic efficiency is as high as 97%, and can be kept stable for 500 cycles. Therefore, the method proposed by the present invention can be used to prepare a nickel-zinc alkaline battery with high capacity and good stability.

[0053] from Figure 4It can be seen that the surface morphology of the unprotected commercial zinc oxide and the prepared nano zinc oxide electrode has changed significantly after cycling, and a large number of needle-like structures with a length of several microns and a diameter of tens of nanometers have appeared, indicating that unevenly deposited zinc dendrites have been produced. However, no obvious morphological changes were observed in the zinc oxide negative electrode protected by the carbon coating layer and the double protection of the carbon coating and the thin film layer after cycling, and the particle structure was still maintained. This result shows that under the action of the protective layer, the deposition of zinc is effectively confined to the carbon protective layer, avoiding the uneven deposition of zinc and effectively inhibiting the growth of zinc dendrites. At the same time, under the further protection of the coating layer, the hydrogen evolution reaction is suppressed, and the self-reaction problem of the zinc oxide negative electrode is significantly improved. Therefore, the method of the present invention can be used to prepare a dendrite-free nickel-zinc alkaline battery with high use capacity, high coulombic efficiency and long service life.

[0054] In summary, the method for making the negative electrode of the nickel-zinc alkaline battery of the present invention adopts synthetic carbon-coated nano zinc oxide, and coats a thin film protective layer on the pole piece, and assembles it into a soft-pack battery with a commercial nickel positive electrode, which inhibits the generation of zinc dendrites and greatly improves the cycle stability of the nickel-zinc battery. The present invention, by taking advantage of the dual effects of carbon coating and PVA thin film protective layer, largely solves the problems of electrode material self-reaction, zinc dendrites and hydrogen evolution that have long been trapped in the zinc negative electrode in an alkaline environment, and significantly improves the coulomb efficiency and service life of the alkaline nickel-zinc battery.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0056] Comparative Example 2

[0057] The difference from Example 4 is that the dried carbon cloth is immersed in PVA gel of other concentrations. When the PVA gel is too thick or too thin, the electrode cannot be coated, and the effect is not ideal.

Claims

1. A method for preparing a negative electrode sheet of a nickel-zinc alkaline battery, characterized in that: The following steps are involved: A1: Preparation of negative electrode materials: Mix the negative electrode active material, conductive agent and binder in proportion, add solvent and stir for 10-15 hours to obtain a uniform slurry; A2: Adding negative electrode material: Add the slurry dropwise and / or apply it on the current collector, and then dry it to obtain the electrode sheet; A3: Preparation of negative electrode: put the electrode in A2 into the soaking solution for 1-5 minutes, and obtain the negative electrode after drying; The negative electrode active material in step A1 is carbon-coated zinc oxide, the concentration of the soaking solution in step A3 is 0.0875 g / mL, the soaking solution is a polyvinyl alcohol solution, and the polyvinyl alcohol is type 1799; The preparation method of the carbon-coated zinc oxide comprises the following steps: (1) mixing zinc salt and oxalic acid, and grinding for 30 to 60 minutes to obtain zinc oxalate; (2) heating the zinc oxalate obtained in step (1) to 300-450° C. at a rate of 3-5° C. / min, keeping the temperature for 30-60 min, and cooling to room temperature to obtain zinc oxide; (3) The zinc oxide and carbon source prepared in step (2) are heated to 800°C at a rate of 2°C / min under a nitrogen atmosphere and kept at that temperature for 2-5 hours. The mixture is cooled to room temperature and then taken out to obtain carbon-coated zinc oxide.

2. The method according to claim 1, characterized in that In step A1, the weight ratio of the negative electrode active material, the conductive agent and the binder is (70-90): (5-20): (5-20), and the ratio of the mass of the solvent to the total mass of the negative electrode active material, the conductive agent and the binder is (10-15):

1.

3. The method according to claim 2, characterized in that In step A1, the conductive agent is acetylene black, the binder is one or more of polyvinylidene fluoride, polyvinyl alcohol, hydroxymethyl cellulose and styrene-butadiene rubber; the solvent is water or ethanol or N-methylpyrrolidone or dimethylacetamide; in step A2, the current collector is carbon cloth or graphite paper or copper mesh, and the drying condition is drying at 80-100°C for 12±6h; and in step A3, the drying is room temperature drying.

4. The method according to claim 1, characterized in that: The zinc salt in step (1) is zinc acetate or zinc carbonate, and the mass ratio of the zinc salt to oxalic acid is (2-4):

1. The carbon source in step (3) is solid organic matter, and the mass ratio of zinc oxide to the carbon source is 1:(3-6).

5. The method according to claim 4, characterized in that The solid organic matter is one or more of phenolic organic matter, ester organic matter and benzene organic matter.

6. The method according to claim 4, characterized in that The solid organic matter is one or more than two of naphthol, dichlorobenzene and acetic acid glycerol monoester.

7. A negative electrode plate for a nickel-zinc alkaline battery, characterized in that: The method is prepared by any one of claims 1 to 6.

8. Use of the negative electrode sheet according to claim 7 in the preparation of nickel-zinc alkaline batteries.

9. The use according to claim 8, characterized in that: The following steps are involved: The zinc negative electrode sheet, the nickel positive electrode sheet and the separator are combined into an electrode group, which is placed in a soft-pack battery, and the electrolyte is injected into the battery soft pack, and the battery is sealed to obtain a nickel-zinc battery; The diaphragm is a glass fiber diaphragm, the electrolyte in the electrolyte is potassium hydroxide, the solvent is distilled water or membrane filtered pure water, and saturated zinc oxide is added, the electrolyte concentration is 6.0-7.0 mol / L, and the electrolyte volume is 200-400 μL.

Citation Information

Patent Citations

  • Secondary zinc alkaline battery comprising negative electrodes and separators surface-modified with gel electrolyte for coating

    KR1020100056257A